Polityczna gra o prawną regulację procedury in vitro – analiza wybranych aspektów debaty w przestrzeni medialnej - Alicja Łaska-Formejster (Ksiegarnia Akademicka Publishing, 2013)
The politics game for regulation of in vitro fertilisation procedure – the aspects of debate in the media sphere analysis